2011
DOI: 10.3109/01443615.2011.609923
|View full text |Cite
|
Sign up to set email alerts
|

Premature rupture of membranes before 28 weeks managed expectantly: Maternal and perinatal outcomes in a developing country

Abstract: This study aimed to assess outcomes of expectant management for early preterm premature rupture of membranes (PPROM). This retrospective cohort involved 66 women with PPROM <28 weeks managed in a single hospital (1999-2006). Main outcomes were chorioamnionitis, severe maternal morbidity (maternal sepsis, haemorrhage/blood transfusion, hysterectomy or admission to intensive care unit), maternal mortality, low birth weight, preterm birth, neonatal infection and perinatal mortality. Mean gestational ages at PPROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
4
7
1
1
Order By: Relevance
“…In fact, while oligohydramnios has been associated with a higher likelihood of caesarean section due to non-reassuring fetal heart rate patterns [5,12,20] as well as with longer NICU stay [25], our findings revealed similar cesarean section delivery rates and length of NICU stay in AFI ≥ 5 cm and < 5 cm groups. Nevertheless, caesarean section rate (18.8%) in our cohort of women with pregnancies complicated by PPROM at 23-33 weeks' gestation seems in accordance with the likelihood of an increased risk of maternal infection in cesarean sections, particularly in women at risk of developing chorioamnionitis [23,26].…”
Section: Discussionsupporting
confidence: 57%
“…In fact, while oligohydramnios has been associated with a higher likelihood of caesarean section due to non-reassuring fetal heart rate patterns [5,12,20] as well as with longer NICU stay [25], our findings revealed similar cesarean section delivery rates and length of NICU stay in AFI ≥ 5 cm and < 5 cm groups. Nevertheless, caesarean section rate (18.8%) in our cohort of women with pregnancies complicated by PPROM at 23-33 weeks' gestation seems in accordance with the likelihood of an increased risk of maternal infection in cesarean sections, particularly in women at risk of developing chorioamnionitis [23,26].…”
Section: Discussionsupporting
confidence: 57%
“…These criteria had already been highlighted individually in previous studies, particularly for fetal presentation and amniotic fluid quantity . The choice of gestational age threshold was based on the literature . PPROM with complications accounted for 6.4% of the patients in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, we must remember that cesarean sections can increase the risk of maternal infection and its complications, particularly in women at risk of developing chorioamnionitis. 5,7,12 Thus, given the rigorous monitoring of these patients it is likely that the rate of perinatal mortality was due to neonatal sepsis and not compression of the umbilical cord. Another point in favor of mortality, as a result of sepsis, is that the risk of neonatal sepsis was equal to the risk of early neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal mortality was high (18.6%), double that found in a university hospital in Iran, which described a rate of 8.7%, 8 but lower than the 25.7% observed in a university hospital in the southeast of Brazil. 12 The differences in perinatal mortality rates may be due to different conduct protocols for PPROM or even regional differences. It was also observed that when AFI was less than 5.0 cm the risk for perinatal mortality was three times higher.…”
Section: Discussionmentioning
confidence: 99%